#### • Class 11 Physics Demo

Explore Related Concepts

# dividing rational expressions calculator

Question:Does anybody know where I can find an online rational expressions calculator? Multiply, divide, addition, and subtraction.( Already tried mathway.com )

Answers:Try www.wolframalpha.com I entered (1/x + 1/y = ) and this online free program computed (x + y) / xy

Question:I have a lesson in Algebra II explaining how to multiply and divide rational expressions but it isn't as clear as I would like to be and I need help with some of my problems. Thank you, in advance! 4. (z^2-z-6)/(z-6) * (z^2-6z)/(z^2+2z-15) 5. (w^2-16)/(w) * (3)/(4-w) 8. (4x^2y)/(z^3) * (2xyz) 9. (2p^3q^2)/(8p^4q) / (4pq^2)/(16p^4) 11. (y62 + 2y)/(y^2+y-2) / (y+5)/(y^2+4y-5) **I need help on learning how to do these, not just answers. And, please don't waste your time telling me "to do my own homework".**

Answers:Sorry i only have 10 fingers :( jk jk

Question:I'm stuck with what to do here : ( (x+3(2x-1) over x(x+4) *divided by* (-x-3)(2x+1) over x does anyone know what to do, and also how to identify the restrictions? Any help would be appreciated. And I know you flip the second one, but i get confused there : ( Thanks!!

Answers:(x+3)(2x-1) ---------------- ..x(x+4) -------------------- .(-x-3)(2x+1) ---------------------- .....x ....(x+3)(2x-1)............x =-------------------- x --------------------- .......x(x+4)............-(x+3)(2x+1) .........2x-1 =- ---------------- answer// .....(x+4)(2x+1)

Question:i have these examples to study and im getting frustrated. have no clue how to do these! please help! i hve finals tomorrow! MULTIPLICATION: (y^2)/(y-1) * (y^2+y-2)/(y^2-2y) DIVISION: (x-2)/(x+5) / (x+6)/(x^2+11x+30) ADDITION: 7/(a+8) + 7/(a^2-64) SUBTRACTION: (a^2-2a-3)/(a^2-9a+18) - (a^2-5a-6)/(a^2+9a+8)

Answers:1. y /(y-1) * (y +y-2)/(y -2y) = y(y)/(y-1) * (y +y-2)/y(y-2) = y/(y-1) * (y +y-2)/(y-2) = y(y +y-2)/(y-1)(y-2) 2. (x-2)/(x+5) * (x +11x+30)/(x+6) = (x-2)/(x+5) * (x+6)(x+5)/(x+6) = (x-2) * (x+6)/(x+6) = x-2 * 1/1 = x-2 3. 7/(a+8) + 7/(a -64) = 7/(a+8) + 7/(a+8)(a-8) = 7(a-8)/(a+8)(a-8) + 7/(a+8)(a-8) = (7a-56+7)/(a+8)(a-8) = (7a-49)/(a+8)(a-8) 4. (a -2a-3)/(a -9a+18) - (a -5a-6)/(a +9a+8) = (a-3)(a+1)/(a-6)(a-3) - (a-3)(a-2)/(a+8)(a+1) = (a+8)(a-3)(a+1) /(a-6)(a-3)(a+8)(a+1) - (a-3)(a-2)(a-6)(a-3 )/(a+8)(a+1)(a-6)(a-3) = [(a+8)(a-3)(a+1) -(a-3)(a-2)(a-6)(a-3)]/ (a+8)(a+1)(a-6)(a-3)